A vivência da presença social : histórias de um curso online para professores de inglês - Menezes, Ana Maria Camin de (2014)
We commonly hear sentences labeling the virtual learning environment and all interaction which takes place on the web in a negative way. My experience in the virtual environment has made me feel differently. For me, it s a space where I meet people to learn together. This research has the objective to observe and analyze how participants of an online course live and feel the social presence and how different views of this concept can influence the teaching and the learning process. The research was developed throughout an online course moderated by me via the Federal University of Uberlândia offered to twenty English teachers from different areas in Brazil where three teacher-students were direct participants. The field texts were composed by diaries written by me during the moderation of the online course, messages exchanged between participants throughout the course, my autobiographical stories, posts written by participants on their individual e-portfolio, the recordings of our synchronous classes, e-mails exchanged by us during and after the online course and texts written by participants. The literature review brings studies on social presence (SHORT et al., 1976; GUNAWARDENA, 1995; WALTHER, 1996; GARRISON et al., 2000; TU, 2002; SWAN, 2003; LOWENTHAL, 2010), on interaction (HILLMAN, WILLIS; GUNAWARDENA, 1994; MOORE; KEARSLEY, 2005), on learning communities (WENGER, 1998; GARRISON, ANDERSON; ARCHER, 2000; GARRISON, 2006; WENGER; WHITE; SMITH, 2009) as well as on and the presence of teachers and students in the online learning environment (MASON, 1998; BERGE, 2000; MORGADO, 2001; SILVA, 2011). The theoretical-methodological path chosen was Narrative Inquiry (CONNELLY; CLANDININ, 2000; CONNELLY; CLANDININ, 2006; CLANDININ; ROSIEK, 2007; CONNELLY; CAINE, 2013; MELLO, 2005; MELLO, 2013). To compose meaning of our lived experience, I adopt the perspective of Ely, Vinz, Downing e Anzul (1997). Throughout the research, I could observe that each participant lived social presence in a unique way. As I see it, our convictions of what it means to be present in an online environment have shaped both the way we lived the experience, as well as how we choose to teach and learn online. I believe the results of this research can bring forth reflections and discussions about social presence and its role in online courses.